2018
DOI: 10.3390/ijgi7080325
|View full text |Cite
|
Sign up to set email alerts
|

Journey-to-Crime Distances of Residential Burglars in China Disentangled: Origin and Destination Effects

Abstract: Abstract:Research on journey-to-crime distance has revealed the importance of both the characteristics of the offender as well as those of target communities. However, the effect of the home community has so far been ignored. Besides, almost all journey-to-crime studies were done in Western societies, and little is known about how the distinct features of communities in major Chinese cities shape residential burglars' travel patterns. To fill this gap, we apply a cross-classified multilevel regression model on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…A recent exception is a study by Long et al (2018), who demonstrated that urban street robbers in China tend to return to locations of their prior offences to commit subsequent robberies, confirming prior findings from the United Kingdom and The Netherlands. Another exception is a study showing that Chinese burglars who live in communities with a higher average rent, a denser road network and a higher percentage of local residents, commit burglaries at shorter distances from their homes (Xiao et al 2018). However, Chinese studies in environmental criminology are still rare, and one of the contributions of the present paper is to add to this developing literature.…”
Section: Introductionmentioning
confidence: 92%
“…A recent exception is a study by Long et al (2018), who demonstrated that urban street robbers in China tend to return to locations of their prior offences to commit subsequent robberies, confirming prior findings from the United Kingdom and The Netherlands. Another exception is a study showing that Chinese burglars who live in communities with a higher average rent, a denser road network and a higher percentage of local residents, commit burglaries at shorter distances from their homes (Xiao et al 2018). However, Chinese studies in environmental criminology are still rare, and one of the contributions of the present paper is to add to this developing literature.…”
Section: Introductionmentioning
confidence: 92%
“…Road network is an important indicator of accessibility. The road network determines the flow pattern of people and vehicles, which has been proven to be closely related to crime [45,46]. Some studies found that the impact of roading was negative [16], while others found it was positive [29,47].…”
Section: Discussionmentioning
confidence: 99%
“…Wellbeing. Five issue papers focused on another aspect of urban human wellbeing: comfort [53][54][55] and crime [56,57]. The former contributions focused on sentiment analysis; the latter two used spatial and machine learning methods, respectively.…”
Section: The Contributions Of This Special Issuementioning
confidence: 99%
“…Bielik et al [55] performed an empirical study to assess trade-offs in a variety of urban design parameters-social, psychological, and energetic-on planning the fundamental elements of urban form: the street network and the building massing. Concerning crime, Xiao et al [56] analyzed the travel patterns of residential burglars in a Chinese city, disentangling origin and destination effects, while Lin et al [57] explored different machine learning algorithms demonstrating the importance of geographic feature design for improving performance and explanatory ability in grid-based crime prediction.…”
Section: The Contributions Of This Special Issuementioning
confidence: 99%